THE LIGHT OF ACEH: BAITURRAHMAN PUSAT PROMOSI PARIWISATA RELIGI DI PROVINSI ACEH - Asmaunizar Asmaunizar (Jurnal Komunikasi dan Media, 2026)
The Aceh provincial government has launched The Light of Aceh as a tourism branding strategy to highlight Aceh’s Islamic identity and cultural heritage. Within this framework, the Baiturrahman Grand Mosque emerges as the central icon of religious tourism promotion. This study aims to analyze the historical significance, architectural uniqueness, socio-economic contributions, and symbolic values of Baiturrahman in strengthening Aceh’s tourism identity. Using a qualitative descriptive method, the research draws on secondary data from academic studies, government reports, and tourism publications. Findings show that Baiturrahman serves not only as a religious site but also as a representation of Aceh’s resilience, particularly during colonial struggles and the 2004 tsunami. Its distinctive architecture featuring black domes, Islamic ornamentation, and monumental umbrellas enhances its appeal for domestic and international tourists. Moreover, the mosque contributes to local economic empowerment through halal tourism activities while reinforcing Aceh’s image as the “Veranda of Mecca.” This study concludes that Baiturrahman plays a vital role in the success of The Light of Aceh as a destination branding initiative, combining spirituality, culture, and history into a unified narrative. Recommendations highlight the need for sustainable tourism management, community empowerment, and broader international promotion of Aceh’s religious tourism.